Classification of Conditioning Regimens for Bone Marrow Transplantation: Historical Background and Current Perspectives - KN Melkova; GD Petrova; NV Gorbunova; TZ Chernyavskaya; OP Trofimova (Клиническая онкогематология)
Hematopoietic stem cells transplantation is a current standard treatment for many oncohematological diseases. The milestone of any type of transplantation is the choice of conditioning regimen. This article presents the principles of classification of conditioning regimens in terms of myeloablativity and discusses the concepts of “autologous transplantation”, “high-dose chemotherapy supported by hematopoietic stem cells”, “allogeneic transplantation” and “immunotherapy”. Up-to-date uniform classification of conditioning regimens may serve an important prognostic component in assessing both the risks and efficacy of hematopoietic stem cells transplantation.